The Cultural Memory of the Lebanese Civil War-Revisited - Dakhli, Leyla,; Wieland, Klaus, (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
This volume, edited by Leyla Dakhli and Klaus Wieland, is an overview of the cultural memory of the Lebanese Civil War, as it has emerged and evolved over the last 30 years. These narratives represent a counter-memory to the non-existent national memory, undesired by Lebanon's political class. In 1991, the Amnesty Law G84/91 was enacted, granting state power impunity for all war crimes, including crimes against humanity. The general amnesty entailed partial amnesia; the war was to be "officially" forgotten. And yet, since the 1990s, nongovernmental organizations, archives, activists, publicists, visual artists, filmmakers, and writers have produced an impressive alternative culture of remembrance of the Lebanese Civil War, which is revisited and analyzed in this book. Contributors represent a multi-disciplinary mix, with perspectives from area studies, history, social science, literary studies, trauma and memory, and peace and conflict studies. See Less